Characterization of Genetic Polymorphisms CYP2R1 rs2060793 and CYP2R1 rs12794714: Potential Biomarkers in Endometriosis Predisposition - Varandas, Tatiana; Dias, Francisca; Sousa, Ana; Sousa, Maria; Medeiros, Rui (Proceedings of Research and Practice in Allied and Environmental Health, 2023)
Background: Endometriosis is an estrogen-dependent gynecologic disorder defined by the presence of endometrium outside the uterine cavity [1, 2]. Vitamin D is a steroid hormone known for its importance in various biological processes [3]. Vitamin D may play a direct role in the changes that the endometrium undergoes during the menstrual cycle, as endometrial tissue also expresses enzymes involved in metabolism [3, 4]. The study of genetic polymorphisms in the genes of vitamin D metabolism, namely CYP2R1 rs2060793 and CYP2R1 rs12794714, may contribute to a better understanding to the development of endometriosis and become potential biomarkers of the disease [5, 6]. Objectives: To evaluate the applicability of CYP2R1 rs2060793 and CYP2R1 rs12794714 polymorphisms as potential biomarkers of genetic predisposition to the development of endometriosis. Methods: A case-control study was carried out that included the analysis of 482 women recruited between 2011 and 2018 in two public hospitals in Rio de Janeiro, Brazil, as part of the "Cooperation Protocol" between UEZO and CI-IPOP. Genetic polymorphisms were analysed by allelic discrimination with the StepOnePlusTM real-time PCR system using TaqManTM probes. Results: There was an association between women carrying the A allele of CYP2R1 rs12794714 polymorphism and early development of endometriosis in about 10 years (p=0.026). We also found that women carrying the A allele of the CYP2R1 rs12794714 polymorphism along with a BMI<30, caucasian women, and without ovarian disease developed endometriosis 10 years (p=0.031), 14 years (p=0.013), and 15 years (p=0.004) earlier, respectively, than women with the GG genotype. Conclusion: Although endometriosis appears at older age, there are factors that may be associated with the development of this pathology at an earlier age. The influence of genetic background, present from birth, seems to be of fundamental importance in the development of the disease at an early age. The allele A of CYP2R1 rs12794714 polymorphism could become a potential biomarker for disease prognosis.